The Influence of Leadership Managerial Abilities and Organizational Climate on Personnel Performance in The Identification and Socialization Unit of The Special Detachment 88 Anti-Terrorism Police of The Republic of Indonesia - Nurul Rohim; Zulkifli Rangkuti; Eddy Hermawan Hasudungan Panjaitan (Dinasti International Journal of Management Science, 2026)
The aim of the research is to describe and analyze the influence of the managerial abilities of leaders which have a significant influence on personnel performance, to find out the influence of organizational climate which has a significant influence on personnel performance and the influence of the managerial abilities of leaders and organizational climate. simultaneously affect performance personnel. The calculated t value for variable X1 (leadership managerial ability) is 6.196 while the t table value for n = 62 is 1.998. So, calculated t > t table or 6.196 > 1.998, it can be concluded that partially the variable Leadership managerial ability has an effect on employee work effectiveness, the calculated t value of variable X2 (organizational climate) is 8.186, while the t table value for n = 62 is 1.998. So the calculated t > t table or 8.186 > 1.998, it is concluded that the organizational climate partially influences the effectiveness of employee work. Thus, H0 is rejected and Ha is accepted, and it is concluded that there is a positive and significant influence between the variable X2 and the variable Y, the calculated F value is 131.225 which is greater than the F table of 2.75 with a significant level of 0.000 because 0.000 < 0.05, it can be said that the variable of the managerial ability of the leader (X1) and the variable of the organizational climate (X2) together influence the performance of personnel (Y).